Alice in Wonderland syndrome (AIWS). A reflection (2018)
The Alice in Wonderland syndrome is a rare clinical neurological condition, defined by the presence of perception disorders usually interpreted by the affected patient as rare metamorphosing and depersonalization phenomena. Due to its extremely rare occurrence and its surreal and sometimes psychedelic character, the syndrome has been associated with the phenomena experienced by Alice, the character in the classic and world-famous story by Lewis Carroll. Copyright © 2018 Sociedad Colombiana de Anestesiología y Reanimación (S.C.A.R.E.). Published by Wolters Kluwer. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).